The Asian City: Processes of Development, Characteristics and Planning
XV, 392 p.
Keywords: In The Asian City the Asian urbanisation processes, nature and characteristics of the 1990s have been analyzed by countries, by comparing different countries and in an international context. The authors are urban specialists from four continents. This volume has been divided into six parts: Part I Urbanisation in an international context; Part II Comparative urban setting; Part III Urbanisation characteristics by country; Part IV Urban planning; Part V The urban poor, and Part VI Perspectives on urbanization. This work allows the reader to understand Asian urban forms, their evolution, the nature of urbanisation, its impact on economic growth in cities, the living and working conditions of the poor, and urban planning and problems.